Investigation Of The Effects Of Lack Of Access To Sufficient Food On Average Lifestyle In Low-Income Countries By Panel Data Analysis Method - Akbulut, Fevzi; Korkmaz, Katip; Şenol, Osman (Fırat Üniversitesi, 2023)
Today, despite the decrease in agricultural areas, problems such as the continuous increase in population, poverty, pandemic, wars and global warming made food insecurity and access to clean water resources even more important. Thus, the effect of not having enough food on the average life expectancy was investigated. In the study, panel data analysis method was used and 58 countries in low and low-middle income groups were analyzed. In the study, panel data analysis method was used and 58 countries in low and low-middle income groups were analyzed. In this direction, it is aimed to determine what kind and in what direction indicators related to access to insufficient food have on the average life expectancy. As a result of the research, it is predicted that a 1% increase in the rate of malnourished population may cause a 0.04% decrease in the average life expectancy, a 1% increase in depth of food deficit may cause in a 0.09% decrease in average life expectancy, a 1% increase in extreme poverty may cause in a 0.18% decrease in average life expectancy. Finally, no significant relationship was found between the number of unsafe water-related deaths and the average life expectancy among the total deaths.

Günümüzde tarım alanlarının azalmasına karşın nüfusun sürekli artması, yoksulluk, pandemi, savaşlar ve küresel ısınma gibi sorunlar gıda güvencesizliğini ve temiz su kaynaklarına erişimi daha da önemli hale getirmiştir. Bu sebeple bu çalışmada yeterli gıdaya ulaşamama durumunun ortalama yaşam süresi üzerindeki etkisi incelenmiştir. Çalışmada panel veri analizi yöntemi kullanılmış, düşük ve düşük-orta gelir grubunda yer alan 58 ülke analiz edilmiştir. Bu doğrultuda yetersiz gıdaya erişim ile ilgili göstergelerin ortalama yaşam süresi üzerinde ne tür ve ne yönde bir etkiye sahip olduğunun tespit edilmesi amaçlanmıştır. Araştırma sonucunda gıda açığı derinliğinde oluşabilecek %1 düzeyinde bir artışın ortalama yaşam süresinde %0,09’luk bir azalışa, aşırı yoksulluk düzeyinde oluşabilecek %1’lik bir artışın ortalama yaşam süresinde %0,18’lik bir azalışa, yetersiz beslenen nüfus oranında oluşabilecek %1’lik bir artışın ortalama yaşam süresinde %0,04’lük bir azalışa sebep olabileceği öngörülmektedir. Son olarak toplam ölüm içerisinde güvenli olmayan su kaynaklı ölüm sayısı ile ortalama yaşam süresi arasında anlamlı bir ilişki tespit edilememiştir.
DÜŞÜK GELİR GRUBU ÜLKELERDE YETERLİ GIDAYA ULAŞAMAMANIN ORTALAMA YAŞAM SÜRESİNE ETKİSİNİN PANEL VERİ ANALİZ YÖNTEMİ İLE İNCELENMESİ